Implementasi Metode Total Physical Response (TPR) Dalam Pembelajaran Maharah Kitabah - Sahkholid Nasution; Lola Irnis Lorenza; Aulia Unnisa; Ja'alna Salwinur Baeha; Andini Rahmawati; Adil Rambe (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Writing skills (maharah al-kitabah) are the highest of the four language skills. Writing is an activity that is related to the thinking process and expression skills in written form. Maharah Kitabah or also known as applied writing has a very important role in human life. Even in educational institutions, learning a foreign language is the main aim of writing skills. In general, writing skills have unique characteristics compared to other types of skills that have an impact on teaching methods. Therefore, every educator needs to look for effective writing teaching methods to improve student achievement. The most effective is the Total Physical Response method or known as Perfect Physical Response (TPR). In the 1960s, American psychologist James Asher developed the TPR method. This research uses a qualitative method, descriptive research type. In other words, this method provides comprehension practice through the use of physical drawing techniques during foreign language teaching at the initial level. This method has the following principles: First, teaching must reduce productive skills in language learning (spoken and written). Second, delay teaching speaking before the child's understanding has developed. Third, language skills acquired through hearing transfer to other skills (speaking, reading and writing). Fourth, teaching must emphasize the meaning of form.